Peningkatan Mutu Tanaman Obat Keluarga (TOGA) untuk Meningkatkan Imunitasi pada Masa Pandemi Covid-19 di Desa Kalisegoro Kecamatan Gunungpati Kota Semarang - Atalia Tamo Ina Bulu; Ayu Ina Solichah; Wahyu Setiyaningsih; Sandi Mahesa (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
TOGA is a restorative plant that can be used locally. This plant, if used and applied appropriately and accurately, will have an impact on the surrounding environment, especially during the COVID-19 pandemic. A good use of TOGA can directly affect a person's endurance. The aim is to provide an understanding to the public about TOGA (Family Medicinal Plants) which can improve health in the community. The implementation of community service activities is carried out using counseling and demonstration methods. The place used is a resident's house in the village of RW 2, Kalisegoro Village, Gunungpati District, Semarang City. The activity was held on May 15, 2022 with 50 female participants. Results Community service activities went well and smoothly starting from licensing to the implementation process of counseling and closing. Conclusion Participants get direct benefits on how to apply TOGA (Family Medicinal Plants) to increase immunity.